The puzzle of transitional justice in Ukraine - Bachmann, Klaus (International journal of transitional justice, 2017)
After the Maidan uprising and the fall of President Viktor Yanukovych, the Ukrainian parliament passed a number of transitional justice measures, including criminal trials and vetting of public employees, members of the law enforcement agencies and the judiciary. Despite strong public demand for retribution, only a limited number of suspects have so far been punished under the new laws. This article examines whether the way transitional justice in post-Maidan Ukraine has been carried out corroborates the assumption that can be derived from the transitional justice literature about the scope of retribution after negotiated transitions. It argues that transitional justice in Ukraine is generally better explained by ‘the politics of the present’ than by the ‘politics of the past,’ but that additional and so far underresearched factors shaping transitional justice outcomes should be included: administrative capacities and traditions and the nexus between a transitional government’s international commitments and the role of the judiciary, especially with regard to large-scale vetting policies.